Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Donald Fischbach, Linda Fischbach, Judge Leonard Meyers, Dorothy Meyers, Deborah Slaybaugh, Martin Tuttle, Robert Fishman, and Linda Fishman